Correlation of dystonia severity and iron accumulation in Rett syndrome - Jan, Tz-Yun; Wong, Lee-Chin; Yang, Ming-Tao; Huang, Chien-Feng Judith; Hsu, Chia-Jui; Peng, Steven Shinn-Forng; Tseng, Wen-Yih Isaac; Lee, Wang-Tso (Scientific reports, 2021)
Individuals with Rett syndrome (RTT) commonly demonstrate Parkinsonian features and dystonia at teen age; however, the pathological reason remains unclear. Abnormal iron accumulation in deep gray matter were reported in some Parkinsonian-related disorders. In this study, we investigated the iron accumulation in deep gray matter of RTT and its correlation with dystonia severity. We recruited 18 RTT-diagnosed participants with MECP2 mutations, from age 4 to 28, and 28 age-gender matched controls and investigated the iron accumulation by susceptibility weighted image (SWI) in substantia nigra (SN), globus pallidus (GP), putamen, caudate nucleus, and thalamus. Pearson’s correlation was applied for the relation between iron accumulation and dystonia severity. In RTT, the severity of dystonia scales showed significant increase in subjects older than 10 years, and the contrast ratios of SWI also showed significant differences in putamen, caudate nucleus and the average values of SN, putamen, and GP between RTT and controls. The age demonstrated moderate to high negative correlations with contrast ratios. The dystonia scales were correlated with the average contrast ratio of SN, putamen and GP, indicating iron accumulation in dopaminergic system and related grey matter. As the first SWI study for RTT individuals, we found increased iron deposition in dopaminergic system and related grey matter, which may partly explain the gradually increased dystonia.